1986
DOI: 10.1159/000234146
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Immunoassay with Cell Suspensions: Studies on Reactions between Serum Antibodies and Cell-Surface Antigens

Abstract: The following reactions of serum antibodies with cell surface antigens were studied by means of an enzyme immunoassay with cell suspensions: (1) Rh antiserum with human red blood cells; (2) H-2 antisera with murine red blood cells; (3) H-2 antisera with murine thymocytes and hepatocytes; (4) Thy-1 antiserum with murine thymocytes; (5) polyvalent and monovalent HLA alloantisera with human leukocytes and human mononuclear cells, and (6) antisera of murine origin with human and marmoset lymphoid cell lines. In al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…28 The data are shown as a mean of the duplicate samples (SD, < 10%). The mean nor¬ mal value as determined in the study of 50 healthy subjects (see IL-2R test kit instruction manual) and confirmed in this study (data not shown) was 573 U/mL (upper limit of normal, 919 U/mL; mean+2 SDs).…”
Section: Detection Of Sil-2rmentioning
confidence: 99%
“…28 The data are shown as a mean of the duplicate samples (SD, < 10%). The mean nor¬ mal value as determined in the study of 50 healthy subjects (see IL-2R test kit instruction manual) and confirmed in this study (data not shown) was 573 U/mL (upper limit of normal, 919 U/mL; mean+2 SDs).…”
Section: Detection Of Sil-2rmentioning
confidence: 99%